Partial Discharge yang Merusak Isolasi SF6 pada Gas Insulated Switchgear (GIS) Tiga Fasa Pengaruh Keberadaan Partikel Asing - Abednego Setiabudi Sianturi; Josie Sidharta (Universitas Islam Lamongan, 2021)
This paper analyzes the effect of the presence of foreign particles on an equilateral arrangement of 3 phase gas insulated switchgear (GIS) insulation equipment. Gas Insulated Switchgear (GIS) that uses SF6 insulation, partial discharge will occur as the insulation ages and there are several other factors that affect the insulation. Partial Discharge needs to be detected to avoid failures that cause damage to equipment in theGIS. In this calculation, the electric field characteristics will be analyzed in 3-phase equilateral GIS by varying the location of the particles in the GIS tank. Particles are modeled to have a length of 5 mm and a thickness of 0.5 mm located in a 3 phase GIS equilateral arrangement with a tank diameter of 150 mm and a conductor diameter of 25 mm. The electric field calculations are reviewed at several points in the 3-phase equilateral GIS tank. The simulation and calculation of the electric field were calculated with FEM method software. The results of the calculations show that thereare differences in the characteristics of the electric field between normal GIS and GIS where foreign particles are present. The difference in these characteristics can be seen in the magnitude of the electric field, and the ratio of eccentricity from some point of view.